2015
DOI: 10.3960/jslrt.55.127
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid Dendritic Cells Producing Interferon-α (IFN-α) and Inducing Mx1 Play an Important Role for CD4<sup>+ </sup>Cells and CD8<sup>+</sup> Cells in Necrotizing Lymphadenitis

Abstract: We confirmed the characteristic clinical features of necrotizing lymphadenitis (NEL) in 66 cases (23 male, 43 female) in Japan, which included high fever (38-40°), painful cervical lymphadenopathy (62/66, 93.9%), and leukopenia (under 4,000/mm(3)) (25/53, 47.2%), without seasonal occurrence, in a clinicopathological, immunohistochemical, electron microscopic serological study. Patient age varied from 3-55 years, and 72.7% (44/66) of patients were younger than 30 years. Histopathology of NEL was characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 22 publications
0
20
0
2
Order By: Relevance
“…pDCs have been associated with a variety of reactive lymph node conditions. 17,38,39 Kishimoto et al 15 first suggested increased numbers of pDCs in a small cohort of KFD patients. Pilichowska et al 16 and Rollins-Raval et al 17 described similar findings in KFD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pDCs have been associated with a variety of reactive lymph node conditions. 17,38,39 Kishimoto et al 15 first suggested increased numbers of pDCs in a small cohort of KFD patients. Pilichowska et al 16 and Rollins-Raval et al 17 described similar findings in KFD patients.…”
Section: Discussionmentioning
confidence: 99%
“…pDCs have been associated with a variety of reactive lymph node conditions 17,38,39 . Kishimoto et al 15 .…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Moreover, histological specimens contained a focal necrotic area.1 Immunohistochemical study also demonstrated myeloperoxidase-positive macrophages, which is one of the characteristic immunological findings of KD. [8][9][10] However, the presence of epithelioid histiocytes and cells with plasma cell differentiation, and absence of tingible body macrophages with crescent-shaped nuclei and plasmacytoid dendritic cells in this case are different from KD. 9,10 Immunohistochemical study demonstrated mixed nature of large lymphoid cells are also different from KD.…”
mentioning
confidence: 84%
“…[8][9][10] However, the presence of epithelioid histiocytes and cells with plasma cell differentiation, and absence of tingible body macrophages with crescent-shaped nuclei and plasmacytoid dendritic cells in this case are different from KD. 9,10 Immunohistochemical study demonstrated mixed nature of large lymphoid cells are also different from KD. 1 Stanley described numerous tingible body macrophages in 2 of 10 cases by cytological examination.…”
mentioning
confidence: 84%
“…However, it may be related to viral infection, as inferred from clinicopathological findings. [1][2][3][4][5][6][7][8] With NEL, innumerable plasmacytoid dendritic cells (PDCs) are observed in lymph nodes. The PDCs produce large quantities of interferon-α (IFN-α).…”
Section: Introductionmentioning
confidence: 99%